2020
DOI: 10.1155/2020/7236534
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Sugar and Organic Acid of Fruit Juices: A Comparative Study and Implication for Authentication

Abstract: A comparison of sugar and organic acid profiles among different fruit juices (including apple, pear, peach, grape, sweet cherry, strawberry, and blueberry with various varieties) was performed to assess the possibility for authentication coupled with chemometrics. It was found that the distribution of each sugar and organic acid in juices showed some specific characteristics related to fruit species, despite the fact that great differences in the content existed among different varieties. Sucrose was the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 36 publications
6
45
0
Order By: Relevance
“…No significant differences in total quantified sugar contents were found between apples and pears, whereas the total quantified organic acid contents of pears were significantly lower than those of apples. 16 Pear has been reported to contain the highest amount of sorbitol among certain fruit juices (apple, pear, peach, grape, sweet cherry, strawberry, and blueberry). 16 Aroma compounds also played an important role in affecting overall flavor of pear fruits, which determined the consumer perception and acceptability of the final pear products.…”
Section: Introductionmentioning
confidence: 99%
“…No significant differences in total quantified sugar contents were found between apples and pears, whereas the total quantified organic acid contents of pears were significantly lower than those of apples. 16 Pear has been reported to contain the highest amount of sorbitol among certain fruit juices (apple, pear, peach, grape, sweet cherry, strawberry, and blueberry). 16 Aroma compounds also played an important role in affecting overall flavor of pear fruits, which determined the consumer perception and acceptability of the final pear products.…”
Section: Introductionmentioning
confidence: 99%
“…Organic acids, being the important constituent of fruit taste along with sugars, strongly influence the organoleptic quality of fruits [4,5]. The sugar-acid ratio is one of the important indicators to measure the flavor and maturation of fruit and is mainly affected by organic acid contents [6][7][8][9]. Many studies have been reported to ascertain compositional changes in passion fruit, and most of these studies have focused on the volatile compounds [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…HPLC analysis of soluble sugars in grape juice was performed by using an e2695 HPLC system coupled with a 2414 refractive index detector (Waters Corp., Wilford, MA, USA) according to the method described in a previous research. [30] A Waters Sugar-Pak I column (6.5 × 300 mm) was used to separate the sugars under the temperature of 80°C with EDTA-Na 2 -Ca solution (50 mg/L) as elution solvent. Chromatograms were recorded and compared with those of sucrose, glucose, and fructose standards.…”
Section: High Performance Liquid Chromatography (Hplc) Analysis Of Soluble Sugarsmentioning
confidence: 99%
“…HPLC analysis of organic acids in grape juices was performed by using an e2695 HPLC system coupled with a 2489 UV/Vis detector (Waters Corp., Wilford, MA, USA) according to the method described in a previous research. [30] A Welch Ultimate AQ-C18 column (4.6 × 250 mm, 5 µm, Welch Science &Technology Co., Ltd, Shanghai, China) was used to separate the organic acids with (NH 4 ) 2 HPO 4 solution (0.02 mol/L, pH 2.4) as elution solvent. Chromatograms were recorded at 210 nm and compared with those of standards.…”
Section: Hplc Analysis Of Organic Acidsmentioning
confidence: 99%